The protective roles of NLRP6 in intestinal epithelial cells. (4th December 2018) - Yin, Jiuheng; Sheng, Baifa; Yang, Kunqiu; Sun, Lihua; Xiao, Weidong; Yang, Hua
Abstract: The evolution of chronic inflammatory diseases is thought to be due to a combination of host genetic variations and environmental factors that include the alteration of intestinal flora, termed "dysbiosis." The intestinal mucosal barrier includes a chemical barrier and physical barrier that have important roles in protecting the intestine against inflammatory injury. The chemical barrier includes antimicrobial peptides (AMPs), and the physical barrier includes a mucous layer, a monolayer of intestinal epithelial cells and cell junctions. The intestinal mucosal barrier is not a static barrier, but rather, it strongly interacts with the gut microbiome and cells of the immune system. Correct expression of AMPs, together with mucus and balanced epithelial cell proliferation, prevents the occurrence of disease. NLRP6, a member of the nucleotide‐binding domain, leucine‐rich repeat‐containing (NLR) innate immune receptor family, participates in the progression of intestinal inflammation and enteric pathogen infections. It has become apparent in recent years that NLRP6 is important in disease pathogenesis, as it responds to internal ligands that lead to the release of AMPs and mucus, thus regulating the regeneration of intestinal epithelial cells. This review summarizes the activation of NLRP6 and its protective role in the intestinal epithelial cell.